2001
DOI: 10.1002/bio.611
|View full text |Cite
|
Sign up to set email alerts
|

Screening of chemiluminescence constituents of cereals and DPPH radical scavenging activity of γ‐oryzanol

Abstract: The chemiluminescence (CL) constituents of cereals were detected by CL using the H(2)O(2)-acetaldehyde system. The cereals tested, such as rice, millet and sorghum, exhibited various levels of CL activity. The gamma-oryzanol fraction was extracted from brown rice and separated into four constituents by HPLC. The four constituents were identified as cycloartenyl ferulate, 24-methylenecycroartanyl ferulate, campesteryl ferulate and beta-sitosteryl ferulate. Free radical scavenging activities with 1,1-diphenyl-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Akiyama et al reported similar DPPH • scavenging activity for SFs 1, 2, 5, and 6 and compound 9 (>100 μM). 20 Islam et al, who used a comparable reaction system with ours, also found SFs 1, 2, and 6 and compound 9 had similar DPPH • scavenging activities. 21 In another study, Kikuzaki et al reported that SF 1, SF 2, and ORY (20 μM) had the same DPPH • scavenging capacity, while compound 9 was slightly better than the SFs.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Akiyama et al reported similar DPPH • scavenging activity for SFs 1, 2, 5, and 6 and compound 9 (>100 μM). 20 Islam et al, who used a comparable reaction system with ours, also found SFs 1, 2, and 6 and compound 9 had similar DPPH • scavenging activities. 21 In another study, Kikuzaki et al reported that SF 1, SF 2, and ORY (20 μM) had the same DPPH • scavenging capacity, while compound 9 was slightly better than the SFs.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…The DPPH • scavenging activities of SFs have also been reported in previous studies. Akiyama et al reported similar DPPH • scavenging activity for SFs 1 , 2 , 5 , and 6 and compound 9 (>100 μM) . Islam et al., who used a comparable reaction system with ours, also found SFs 1 , 2 , and 6 and compound 9 had similar DPPH • scavenging activities .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The maintaining or enhancing of the antiradical capacity of phytosteryl phenolates suggests that these derivatives may be used as antioxidants in more lipophilic systems. As one of the main constituents of γ ‐oryzanol, phytosteryl ferulates, including sitosteryl ferulate, and campesteryl ferulate, have been reported to possess high free radical scavenging capacity . In our study, phytosteryl caffeates are the only group of compounds that showed higher radical scavenging capacity than the reference trolox.…”
Section: Resultsmentioning
confidence: 56%
“…Previous research in mammals and livestock has highlighted the beneficial role of Ory in terms of survival and growth [10][11][12]. Besides, Akiyama et al [13] reported Ory's high radical scavenging capacity in mammalian systems. Moreover, studies by Wang et al [10] and Minatel et al [14] demonstrated the Ory is associated with antiinflammatory properties and cholesterol-lowering effects in mammals and livestock, respectively.…”
Section: Introductionmentioning
confidence: 99%